Cardinal August Hlond the spiritual mentor of John Paul II? - Samsel, Robert (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
Josemaria Escrivá, showing the way to holiness, teaches: "Shine like a star ... rise high and shine with light in the sky? Better to burn like a torch, hidden, igniting everything you touch. – This is your apostolate, this is why you live on earth ( Route 385)”( Escriva 2014). The eloquent indication of the founder of Opus Dei may prove helpful in the analysis of a possible bond between the Servant of God Cardinal August Hlond and St. John Paul II and the possible influence of the cardinal on the future pope.The issue of the relationship and possible formative and spiritual influence of Card. August Hlond to Karol Wojtyła is not a new issue. It has been described several times by Fr. Stanisław Kosiński SDB Fr. dr. Bogusław Kozioł Maria Włosek These are studies that deal with the issue we are interested in here, or very broadly - including also Cardinal Wyszyński, historically, be very analytical - limiting yourself to one issue.